Maybe once, maybe twice : a novel - Greenberg, Alison Rose (St. Martin's Griffin, 2023)
"You know that old saying, "if we are still single when we're 35, we should get married?" Well, Maggie Vine made that vow with two different people, at two very different stages of her life. And they both showed up. Maggie Vine's life is going extra-medium. At 35 she's pursuing her dreams of being a singer and being a mother--though neither are successfully panning out. So when Garett Scholl--stifled hedge fund manager by day but electrifying aspiring rock singer by night--comes to her 35th birthday party with the intention to kiss Maggie senseless, it feels like one piece might click into place. Except he's engaged to someone else, and Maggie knows she won't fit into the cookie-cutter life he's building for himself. Enter Asher Reyes. Her first boyfriend from summer camp, turned into heartthrob actor, he's lived a successful yet private life ever since he got famous. When a career-changing opportunity is presented to Maggie after her reconnection with Asher, it feels like everything--music, love, family--will fall into place. But her past won't let her move on without a fight"--